Rancang Bangun Aplikasi Inventory Produksi Kayu Berbasis Web dan Mobile: Studi Kasus UD Sulur Jati - Agustine, Dian Nofita; Handayani, Irma (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
UD Sulur Jati is a company engaged in the production of wooden crafts. Based on the results of the study, this company still uses a manual recording system to store data, which makes the data very vulnerable to the risk of loss or damage. To overcome this problem, this study utilizes technology by developing an inventory application. This application is designed to record product orders, manage raw material inventory before the production process, and record finished goods according to the orders received. The system developed includes a web and mobile platform, where the web application is built using the PHP programming language and can be accessed by administrative staff, while MySQL is used as a database to store information. The mobile application, on the other hand, is developed using Dart and is designed to be accessed by the company owner. The result of this system development is an application that is able to increase the efficiency of the data recording and monitoring process, reduce errors that often occur due to the use of manual recording methods, and increase accuracy and efficiency in inventory management at UD Sulur Jati.